Space, Art and Transcendence - Pinilla Burgos, Ricardo (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
In the light of Heidegger’s analysis of space and art, and its link with a milestone for modern sculpture such as Eduardo Chillida, space is presented, together with time, as a fundamental element of art and especially of sculpture and architecture. Space is not a homogeneous neutral background, but an original phenomenon that compromises from the beginning the creation and the peculiar kind of transcendence to which every work of art invites us. Every work submerges us on one side in a feverish, sensitive and bodily immanence, in the mystery of the sensitive (aesthetic) that we are, but aswell it takes us beyond or nearer than the conventional meanings and relations and our situation. From here, we will consider whether and how we can put the aesthetic experience of space in relation to the transcendence of which religion commonly speaks, illuminated in turn from the study of the sacred of Mircea Eliade.